The Oxford handbook of organizational well-being - Cartwright, Susan, 1951-; Cooper, Cary L. (Oxford University Press, 2009)
Leading international scholars focus on organisational well being in its widest sense, and is concerned with reviewing the factors which are associated with ill health, as well as those which promote positive health and well being.